A sustainable food-system? : economic sustainability of Swedish community supported agriculture (CSA) - Svensson, Annie (SLU/Dept. of Biosystems and Technology (from 130101), 2018)
This research investigates Community Supported Agriculture (CSA) in a Swedish setting. CSA is believed to be a potential way towards a more sustainable food-system where consumers and farmers come together to form local and transparent systems. In Sweden, CSA is still in its infancy, but in the last years there has been a large increase in the number of farms. So far little has been written about CSA in Sweden. The concept has been evaluated as ecologically- and socially sustainable, but the economic dimension of sustainability has been in question. Until now the economic viability of CSA-farms has been low, both in Sweden and internationally. For this reason, this study investigates the economic sustainability of Swedish CSA-farms and how it could be enhanced. To place the research in a bigger perspective, the potential for Swedish CSA to contribute to a sustainable food-system is discussed. An agroecological approach is used where both internal- and external aspects affecting the farms and the CSA-movement are considered. Even if focused on economic sustainability, the study aims to describe CSA holistically without neglecting other dimensions of sustainability. 14 CSA farms were interviewed about their economic situation, their view on profitability and opinions on several aspects believed to have the potential to enhance the economic sustainability of the farms. The result showed that the CSA-farms had difficulties to cover labour costs and had problems with inefficiency, hence the economic sustainability of the farms is weak. At the same time, long-term economic plans had been set-up and the member groups were supportive and loyal. CSA gives the farmers a stable and predictable income and the possibility to know in advance how much they need to produce. Possibly, the low viability of CSA-farms is not connected to the concept itself, but rather an effect of the recent establishment of most farms and that many of the CSA-farmers lack professional farming experience. Consequently, the study did not find some approaches or business models to be more conducive than others to reach higher profitability. Finally, the study concludes that CSA succeeds to create relationships between consumers and farmers, gives the consumer insight into how food is produced and attracts new farmers to the profession. However, in the creation of a sustainable food-system, it would be beneficial if more professional and already established farmers converted into CSA.